Low-dose belimumab for patients with systemic lupus erythematosus at low disease activity: protocol for a multicentre, randomised, double-blind, placebo-controlled clinical trial. Issue 1 (1st February 2022) - Sun, Fangfang; Huang, Wenyan; Chen, Jie; Zhao, Liling; Zhang, Danting; Wang, Xiaodong; Wan, Weiguo; Dai, Sheng-Ming; Chen, Sheng; Li, Ting; Ye, Shuang
Abstract : Introduction: SLE is a chronic inflammatory systemic autoimmune disease with relapsing–remitting pattern. B-lymphocyte stimulator was involved in the pathogenesis of SLE. The humanised monoclonal antibody belimumab with 10 mg/kg was effective for active patients. However, the efficacy of low-dose belimumab for prevention of disease flares in patients with SLE with low disease activity is to be explored. Methods and analysis: This is a multicentre, randomised, double-blind, placebo-controlled clinical trial. Patients who have Safety of Estrogens in Lupus Erythematosus National Assessment–Systemic Lupus Erythematosus Disease Activity Index (SELENA-SLEDAI) scores no higher than 6; with no A score or no more than one B score on the British Isles Lupus Assessment Group (BILAG) scale; and who are treated with prednisone (≤20 mg per day) at screening will be enrolled. 334 adults will be randomly assigned in a 1:1 ratio to receive intravenous 120 mg belimumab or placebo (saline) arm on weeks 0, 2, and 4, and then every 4 weeks until 48 weeks, with standard of care. The primary outcome measure is a composite index of severe or mild-to-moderate disease flares (SELENA-SLEDAI Flare Index) within 52 weeks. Secondary outcomes include the percentage of severe flare, the percentage of mild-to-moderate flare, time to first disease flare, changes in prednisone dose, SELENA-SLEDAI, as well as BILAG score, the percentage of patients achieving prednisone free and safety analysis. Ethics and dissemination: The protocol has been approved by the Ethics Committee of the Renji Hospital, Huashan Hospital and the Sixth People's Hospital. The trial has been registered and the detailed information is available at https://clinicaltrialsgov/ct2/show/NCT04515719 . The results of this clinical trial will be submitted for publication in peer-reviewed journals and key findings will also be presented at national and international conferences. Trial registration number: NCT04515719 .